Asl nusxa va tarjima o‗rtasidagi tafovutlar - Sapayeva, F.D (SCIENCE and SOCIETY, 2024)
This article discusses the main differences between the original text and the translation, the differences between the two languages, and the translation of (similar) alternative words. Issues such as the spiritual closeness of the author and the mutharjim,
Keywords: poem; translator; translation; poetic repetition; verse and clause; meaning; form and content; word; text; poet; Makhtumkuli; the Turkmen language; the Uzbek language